Restoring at landscape scales: Interview with Andrew Bennett - Bennett, A.; McDonald, Tein (Wiley-Blackwell Publishing Ltd, 2017)
© 2017 Ecological Society of Australia and John Wiley & Sons Australia, Ltd Intrigued by the power of science to grapple with questions relevant to management, Victorian landscape ecologist Andrew Bennett has directed his career to investigating how human land-use and landscape change affect native fauna and ecological processes, seeking ways to achieve the ongoing conservation of Australian native fauna.